Earnings Management and Earnings Value Relevance in Indonesia's Property Sector During and Post COVID-19 Pandemic - Wilyan Amri; Widia Astuti (MASI Mandiri Edukasi, 2025)
The COVID-19 pandemic had a significant impact on the property and real estate sector in Indonesia. During the Large-Scale Social Restrictions (PSBB), economic activity declined sharply, resulting in substantial losses for many property companies. This study aims to analyse earnings management and earnings value relevance in real estate companies during and after the COVID-19 pandemic. A descriptive quantitative method was employed using secondary data from the financial statements of 34 companies listed on the Indonesia Stock Exchange. The results of the Kolmogorov–Smirnov (K–S) test indicated that the earnings management variable was normally distributed (significance values during the pandemic = 0.217; post-pandemic = 0.235). Meanwhile, the F-test revealed no significant simultaneous effect of the independent variables (BVPS and EPS) on earnings value relevance in both periods, with a p-value of 1.293 (≥ 0.05). Despite the potentially negative perception of earnings manipulation, such decisions were found to enhance the relevance of earnings and firm value. This study uniquely highlights the pandemic’s impact on accounting practices and the relevance of earnings while also demonstrating corporate strategies to maintain their image and attract investors amid economic uncertainty.